PENGARUH OLAHRAGA FITNES TERHADAP KADAR KOLESTEROL DARAH PADA PESERTA FITNES - Andi Lis Arming Gandini; supriadi supriadi (Poltekkes Kemenkes Kalimantan Timur, 2017)
ABSTRACT Exercise is one way to increase physical endurance as an effort to maintain health and fitness. Physical exercise is one effort to overcome the excess fat as well as to achieve a good level of physical fitness and can improve functional ability. This research is quantitative research, research design using quasi experiment method with pre-test and post-test without control (self-control) design. This study was conducted in April s.d November 2016 which aims to determine the effect of fitness exercise on blood cholesterol levels in fitness participants. Before the intervention done pre-test is to check blood cholesterol levels, then intervene and within 1 month post-test to assess changes in blood cholesterol levels. Result: Sports fitness gives a significant influence on the decrease of blood cholesterol level with p value = 0,013. The result of Multivariate test obtained exponen B = 13,732 compared with food with result of test p = 0,045 food with OR = 0,114. Conclusion: that with sports fitness at least 3 times a week and duration of at least 1 hour have a big effect to decrease blood cholesterol level especially if followed by food which appropriate with nutrient sufficiency value. Suggestion: Sports fitness can be done as an alternative to lower blood cholesterol levels in addition to aerobic exercise. Keywords: exercise, fitness, blood cholesterol levels